Asymptotic Behavior of a Class of Degenerate Parabolic Equations - Hongtao Li; Shan Ma (Abstract and Applied Analysis)
We investigate the asymptotic behavior of solutions of a class of degenerate parabolic equations in a bounded domain () with a polynomial growth nonlinearity of arbitrary order. The existence of global attractors is proved in , , and , respectively, when can be just compactly embedded into () but not .